PENGARUH PENAMBAHAN TITIK GROUND ROD TERHADAP NILAI TAHANAN PENTANAHAN TOWER TRANSMISI SUTT 70kV TES-PEKALONGAN - Rhenol Alexander Siboro; Siti Anisah (CV. Hawari, 2026)
The grounding system is an important part of the installation of the High Voltage Overhead Line (SUTT) transmission tower, which serves to channel the interference current to the ground to maintain human safety and equipment reliability. A low grounding resistance value is needed for the protection system to work optimally. This study aims to analyze the effect of the addition of ground rod points on the grounding resistance value in the 70kV TES-PEKALONGAN SUTT transmission tower. Measurements are made directly using an earth tester. The measurement results show that the addition of ground rod points can significantly reduce the grounding resistance value. Thus, increasing the number of grounding points can be one of the technical solutions to improve the performance of the grounding system on the electricity transmission network.